Equipment pressure applied to geomembrane in composite liner system. Issue 6 (December 2012) - Stark, T.D.; Pazmino, L.F.; McDowell, C.J.; Phaneuf, R.
Abstract : ABSTRACT: This technical paper presents the results of a test pad at an operating municipal solid waste landfill that measured pressures applied to the primary geomembrane in the double composite liner system used at the site. The pressures were measured with two pressure cells placed on top of the geomembrane and covered with varying thicknesses of sandy structural fill and rounded stone, i.e. a leachate collection and removal layer stone. The pressures were applied by two types of dozers to investigate the magnitude of applied pressures and the effect of equipment on the applied pressure. In general, the results show increased pressure with decreasing cover layer thickness, increasing speed, and turning over of the pressure cells. The data can be used to estimate the minimum layer thickness to limit the pressure applied to an underlying geomembrane to a tolerable value, e.g. 41.4 kPa, and prevent geomembrane damage or puncture during construction.